Gender dimensions of agriculture, poverty, nutrition, and food security in Nigeria - Ajani, Olubunmi Idowu Yetunde (International Food Policy Research Institute, 2009)
In Nigeria, women are often marginalized in their access to economic, political, and social resources compared to men, rendering them relatively poorer than their male counterparts. Important differences also exist between women and men in their contributions to agriculture, and in poverty, nutrition and food security levels. This review aims to provide insights into the performance of agricultural activities by gender, and provide a gender analysis of poverty, nutrition, and food security. Gender awareness in these areas is critical in planning programs that seek to reduce poverty and malnutrition, and attain food security in Nigeria. --Authors' Abstract